Pharmacokinetics, pharmacodynamics and safety of empagliflozin, a sodium glucose cotransporter 2 (SGLT2) inhibitor, in subjects with renal impairment - Macha, S.; Mattheus, M.; Halabi, A.; Pinnetti, S.; Woerle, H. J.; Broedl, U. C. (Diabetes, obesity & metabolism, 2014)
Aims Empagliflozin is a selective sodium glucose cotransporter 2 (SGLT2) inhibitor that inhibits renal glucose reabsorption and is being investigated for the treatment of type 2 diabetes mellitus (T2DM). Methods In this open‐label study, the effect of renal impairment on the pharmacokinetics, pharmacodynamics and safety of a 50 mg dose of empagliflozin was investigated in 40 subjects, grouped according to estimated glomerular filtration rate (eGFR). Results Maximum empagliflozin plasma concentrations were similar in subjects with normal renal function and renal impairment. Area under the empagliflozin concentration‐time curve (AUC0–∞) values increased by approximately 18, 20, 66 and 48% in subjects with mild, moderate, severe renal impairment and renal failure/end stage renal disease (ESRD), respectively, in comparison to healthy subjects. This was attributed to decreased renal clearance (CLR). Urinary glucose excretion (UGE) decreased with increasing renal impairment and correlated with decreased eGFR and CLR. Empagliflozin was well tolerated, with no increase in adverse events associated with renal impairment. Conclusions Renal insufficiency resulted in decreased CLR of empagliflozin, moderately increased systemic exposure and decreased UGE. A single 50 mg dose of empagliflozin was well tolerated in subjects with normal renal function and any degree of renal impairment. The pharmacokinetic results of this study indicate that no dose adjustment of empagliflozin is required in patients with renal impairment.